Related Videos

Simplify the expression $\frac{x^5-x^4+x^2-2}{x^2+1}$

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Algebra 2 - Learn how to divide using long division with multiple zeros, (x^5 - 1) / (x - 1)

https://www.youtube.com/watch?v=QLmbtmqii9o

Dividing polynomials by linear expressions | Algebra 2 | Khan Academy

https://www.youtube.com/watch?v=G2VBRwXq1q4

Algebra 2 - Simplify by dividing two rational expressions using factoring (32/n‐8)/(1/n‐8)

https://www.youtube.com/watch?v=wFy0p8Jo6pQ

Simplifying rational expressions 2 | Polynomial and rational functions | Algebra II | Khan Academy

https://www.youtube.com/watch?v=dstNU7It-Ro

Algebra 2-using synthetic division to divide two polynomials with a remainder (x^3‐x^2+9x‐3)/(x‐2)

https://www.youtube.com/watch?v=qzTkg7iFAbU

Using long division to divide polynomials - Math tutorial

https://www.youtube.com/watch?v=Ew1eMrKMVeA
SnapXam A2
Answer Assistant

beta
Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Tips on how to improve your answer:

$\frac{x^5-x^4+x^2-2}{x^2+1}$

Time to solve it:

~ 0.07 s